Non-pharmacological prevention of postoperative delirium by occupational therapy teams: A randomized clinical trial - Alvarez, Evelyn A.; Rojas, Veronica A.; Caipo, Lorena I.; Galaz, Melany M.; Ponce, Daniela P.; Gutierrez, Rodrigo G.; Salech, Felipe; Tobar, Eduardo; Reyes, Fernando I.; Vergara, Rodrigo C.; Egaña, Jose I.; Briceño, Constanza A.; et al. (Frontiers in Medicine, 2023)
Background: Patients who develop postoperative delirium have several clinical complications, such as increased morbidity, increased hospital stays, higher hospital costs, cognitive and functional impairment, and higher mortality. Postoperative delirium is a clinical condition preventable by standard non-pharmacological measures, but in the perioperative period prevention is still deficient. An intensive Occupational Therapy (OT) intervention has been shown to be highly effective in preventing delirium in critically ill medical patients, but it is unknown the effect in surgical patients. Thus, we studied the efficacy of a preventive OT intervention on the incidence of delirium and postoperative subsyndromal delirium in patients older than 75 years undergoing major elective surgeries. Methods: A multicenter, single-blind, randomized clinical trial was conducted between October 2018 and April 2021, at two hospitals in Santiago of Chile. Patients older than 75 years undergoing elective major surgery were eligible for the trial inclusion. While patients with cognitive impairment, severe communication disorder and cultural language limitation, delirium at admission or before surgery, and enrolled in another study were excluded. The intervention consisted of OT therapy twice a day plus standard non-pharmacological prevention intervention during 5 days after surgery. Our primary outcome was development of delirium and postoperative subsyndromal delirium. Results: In total 160 patients were studied. In the interventional group, treated with an intensive prevention by OT, 9 patients (12.9%) developed delirium after surgery and in the control group 4 patients (5.5%) (p = 0.125, RR 2.34 CI95 (0.75-7.27)). Whereas subsyndromal postoperative delirium was present in 38 patients in the control group (52.1%) and in 34 (48.6%) in the intervention group (p = 0.4, RR 0.93 CI95 (0.67-1.29)). A post hoc analysis determined that the patient's comorbidity and cognitive status prior to hospitalization were the main risk factors to develop delirium after surgery. Discussion: Postoperative OT intervention was not superior to standard non-pharmacological prevention in reducing delirium and subsyndromal delirium in adults older than 75 years. Clinicaltrials.gov NCT03704090.